PELAKSANAAN TILANG KENDARAAN BERMOTOR DI KOTA PEKANBARU - Siahaan, Yansen Yohanes; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The high number of traffic violation punishments should be increased. The aim is an implementation of a speeding ticket in order to deter traffic violators from repeating such actions again in the future. However in the process of giving traffic tickets, extortion and bribery practices are encountered to a large scale by traffic violators. Based on this, researchers want to conduct research on the implementation of the Motor Vehicle traffic tickets in Pekanbaru. This study aims to determine the causes of traffic ticket Implementation of Motor Vehicles in the city of Pekanbaru and the factors that affect the implementation of the Motor Vehicles traffic tickets in Pekanbaru.This study uses the concept of implementation theory put forward by George C. Edward, which describes several indicators, namely communication, resources, disposition and bureaucratic structure. This study used a qualitative approach to data collection through the use of interviews, observation and documentation. The informants are the Head of the Bureau of Traffic Police Pekanbaru, the Traffic Police and the community.Based on this research, it is known that the implementation of the tickets as caution and punishment to motorists in the city of Pekanbaru works rather effectively. And the factors influencing it is the integrity of policy implementation, infrastructure and legal awareness in traffic.Keywords: Implementation, Policy Implementation, Vehicle of Traffic Tickets